2019
DOI: 10.1016/bs.aecr.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the resilience of biodiversity-driven functions in agroecosystems under environmental change

Abstract: This paper has been peer-reviewed but may not include the final publisher proof-corrections or pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 279 publications
(434 reference statements)
2
21
0
3
Order By: Relevance
“…It has been suggested that robustness and evenness may be associated with pollination network stability (Martin, Feit, Requier, Friberg, & Jonsson, 2019;Tylianakis, Laliberté, Nielsen, & Bascompte, 2010).…”
Section: The Response Of Pollination Network To Environmental Effectsmentioning
confidence: 99%
“…It has been suggested that robustness and evenness may be associated with pollination network stability (Martin, Feit, Requier, Friberg, & Jonsson, 2019;Tylianakis, Laliberté, Nielsen, & Bascompte, 2010).…”
Section: The Response Of Pollination Network To Environmental Effectsmentioning
confidence: 99%
“…A major determinant of the vulnerability of ecosystem services to environmental change is their resilience to disturbance [1,2]. Resilient ecosystem services can absorb a substantial amount of disturbance before transitioning to an alternate state, whereas services of low resilience are likely to transition when exposed even to a relatively small level of disturbance [2,3]. In addition, resilient ecosystem services can recover faster and/or persist better in response to disturbance than their low resilience counterparts [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The approach is based on the identification of traits involved in plant–bee interactions (i.e. ‘trait matching’, Bartomeus et al 2016 ; Martin et al 2019 ; Klumpers et al 2019 ). For instance, tongue length in bees determines floral resource acquisition: bees with long tongue are expected to visit plants with deep corolla, suggesting a strong matching between flower and bee morphology (Bartomeus et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%